MODEL PENGEMBANGAN HUMAN CAPITAL DALAM KONTEKS MODAL SOSIAL - Widodo, Widodo (Benefit, 2009)
This study aims to examine the effect of in the learning orientation , commitment, the influence of human capital Â on the performance of organization , the influence of commitment to human resource performance and increase in performance of organization in the context of environmental adaptability.The sampling method is purposive sampling and the number of samples is 120. The data analysis technique in this study used the Structural Equation Modelling (SEM) of the software package AMOS 4.0The study shows that when the orientation of the higher learning, the higher the commitment of human resources, if the orientation of the higher learning, the higher the intensity of human capital., When the commitment to the consensus of the higher, the higher the intensity of human capital, Human capital When the higher, the more high-performance organization, the context of high social capital moderates the structure of the equation that makes human capital influence on organizational performance